EFL FUTURE ENGINEERS’ LANGUAGE ANXIETY: FINAL PROJECT PRESENTATIONS AND ORAL EXAMINATIONS : Received: 02nd December 2021; Revised: 10th March 2022, 15th March 2022; Accepted: 22nd March 2022 - Cherni, Thameur; Cherni, Badreddine (PUPIL: International Journal of Teaching, Education and Learning, 2022)
For many years, undergraduate students’ foreign language anxiety (FLA) has been investigated. These students have experienced different levels of FLA due to several variables leading them to feel anxious during final summative examinations. In this context, several EFL future engineers show anxiety when performing classroom final project presentations and oral examinations at ESPRIT, School of Engineering, Tunisia. Despite the significance of FLA for research and researching, few studies missed the correlation between anxiety and final oral assessments in Tunisian academic settings. Thus, the researchers in this study were interested in reviewing the factors and causes of anxiety as experienced by EFL students so that the right strategies can be implemented. This study collected data from 129 participants of both electromechanical and civil engineering second-year students through an adapted version of the Foreign Language Classroom Anxiety Scale (FLCAS) developed by Horwitz, et al. (1986). The results show eight factors and six causes impeding undergraduate students from speaking their minds orally. It follows some implications for language teaching are offered to reduce EFL Future Engineers’ English Language Anxiety while performing Final Project Presentations and Oral Examinations.